Cardiovascular disease prediction: do pulmonary disease-related chest CT features have added value? - Jairam, Pushpa M; de Jong, Pim A; Mali, Willem P Th M; Isgum, Ivana; van der Graaf, Yolanda (European Radiology, 2015)
Objective: Certain pulmonary diseases are associated with cardiovascular disease (CVD). Therefore we investigated the incremental predictive value of pulmonary, mediastinal and pleural features over cardiovascular imaging findings.Methods: A total of 10,410 patients underwent diagnostic chest CT for non-cardiovascular indications. Using a case-cohort approach, we visually graded CTs from the cases and from an approximately 10 % random sample of the baseline cohort (n = 1,203) for cardiovascular, pulmonary, mediastinal and pleural findings. The incremental value of pulmonary disease-related CT findings above cardiovascular imaging findings in cardiovascular event risk prediction was quantified by comparing discrimination and reclassification.Results: During a mean follow-up of 3.7 years (max. 7.0 years), 1,148 CVD events (cases) were identified. Addition of pulmonary, mediastinal and pleural features to a cardiovascular imaging findings-based prediction model led to marginal improvement of discrimination (increase in c-index from 0.72 (95 % CI 0.71-0.74) to 0.74 (95 % CI 0.72-0.75)) and reclassification measures (net reclassification index 6.5 % (p < 0.01)).Conclusion: Pulmonary, mediastinal and pleural features have limited predictive value in the identification of subjects at high risk of CVD events beyond cardiovascular findings on diagnostic chest CT scans.Key Points: • Incidental cardiovascular findings on routine chest CT can predict cardiovascular disease • Non-cardiovascular chest CT abnormalities are associated with cardiovascular disease • Non-cardiovascular chest CT features have limited predictive value beyond cardiovascular features.